Student-Teacher Interpersonal Relations Role in Carrier Advancement (International Journal of Food and Nutritional Sciences, 2022)
Background: This study aims to examine the concept of student-teacher relationships and their interaction with respect to senior secondary students. It also explores the facets and significance of interpersonal relationships on students' development.Method: A survey was conducted among senior secondary students to gather data regarding their perceptions of student-teacher relationships.Findings: The results indicate that the majority of senior secondary students agree or strongly agree that their teachers demonstrate genuine care and concern for their well-being and academic progress. Students also perceive that their teachers create a supportive and inclusive classroom environment, provide constructive feedback and guidance, and respect and value their strengths, interests, and ideas.